EFFECTS OF GEOPOLITICAL RISKS AND POLITICAL UNCERTAINTIES ON STOCK MARKETS: COUNTRY SPECIFIC NEW GENERATION PANEL DATA ANALYSIS FOR DEVELOPING ASIAN COUNTRIES - Sadeghzadeh Emsen, Hatıra (Journal of process management and new technologies, 2022)
In general, there are strong and meaningful relationships between risks and uncertainties, and economic activities. In this context, geopolitical risks (GPR) and global economic and political uncertainties (WUI) can significantly affect financial markets and investor behavior. In this study, the effects of GPR and WUI on stock markets for 10 developing Asian countries were investigated for 2001:M07-2020:M12 period. Cross-section dependency was examined with LM, and tests, series stationarity with Hadri and Kurozumi (2012) test, cointegration relations with Westerlund (2006) cointegration with multiple structural breaks method, and regression analyzes with Eberhardt and Bond (2009) method. It was determined that high GPR decreases the stock market index in Turkey, Korea, Russia, Indonesia and Malaysia, whereas it increases in India, Thailand and Philippines. It was found that high WUI decreases the stock market index in Korea, China, Indonesia and Thailand, whereas it increases in Turkey, India and Malaysia. On the other hand, while the stock market returns of the change in GPR decreases the stock market returns in Turkey, Korea, Russia, Indonesia and Malaysia, it increases in India, Thailand and Philippines. It has been determined that change in WUI decreases the stock return in Korea, China, Indonesia and Thailand, and it increases in Turkey, India and Malaysia. It was also observed that changes in GPR increases the volatility of the stock markets in India, Thailand and Philippines, and it decreases in Turkey, S. Korea, Russia, Indonesia and Malaysia. While the effects of change in WUI increases stock market volatility in Turkey and Malaysia, it decreases in Korea, China, Indonesia and Thailand. As the results achieved are heterogeneous, investors should avoid a basket trading strategy in these countries. Country-specific causality test was carried out with the Konya (2006) method, and it was observed that there are causal relationships between high WUI and stock market index, high WUI and stock market return in Turkey. Similarly, causal relationships were determined between high WUI and stock market index in India, between change in WUI and stock market index volatility in Philippines, between high GPR and stock market index, change in GPR and stock market return in Hong Kong. Causal relationships for all countries in the panel were examined using the Dumitrescu and Hurlin (2012) method, and causality was only found between high WUI and stock market index.